LIPID METABOLISM STATUS IN PATIENTS WITH MECHANICAL JAUNDICE, ACUTE CHOLANGITIS AND BILIARY SEPSIS - Борисенко В. Б. (World of Medicine and Biology, 2014)
Introduction. Mechanical jaundice is sometimes complicated by acute cholangitis and biliary sepsis which are accompanied by hepatic dysfunction development and result in its transformation into hepatic insufficiency. Insufficient study and peculiarity of hepatic dysfunction diagnostics criteria are undoubtedly part of unsatisfactory results of these patients treatment. Aim of the research. Realization of comparative characteristics of lipid metabolism peculiarities in patients with mechanical jaundice, acute cholangitis and biliary sepsis. Materials and methods. The results of 90 patients with mechanical jaundice syndrome study were analyzed. The diagnostics program apart from standard general clinical, laboratory research was supplemented by identification of general cholesterol, β-lipoproteins, triglicerides, lipopolysaccharids of high, low and very low density as well as atherogenicity coefficient at receipt, on the 3rd and 7th day of the study. The instrumental phase included ultrasound research, papilloscopy and endoscopic retrograde cholangiopancreatography. Differential diagnostics of mechanical jaundice, acute cholangitis and biliary sepsis was done according to the program worked out by us with the use of triad of diagnostic criteria: level of blood procalcitonin, SIRS signs, SOFA scale points. Results. Discussion. As a result of the research it was stated that the most frequent (64,4%) reason for mechanical jaundice development was choledocholithiasis, stenosis of the large duodenal papilla was observed less frequently as well as tabular stenosis of the choledoch on the ground of pseudotumor-like pancreatitis, Mirizzi’s syndrome (II type), choledoch strictures, reflux cholangitis and gastric ulcer. The patients were divided into three sub-groups. The first group comprised 24 (26,7%) patients with uncomplicated mechanical jaundice (SIRS-0, SOFA≤ 3, procalcitonin - 0-0,2 ng/ml); the second – 46 (51,1%) with acute cholangitis (SIRS-1, SOFA ≤ 3, procalcitonin - 0,2-1,3 ng/ml); the third - 20 (22,2%) with biliary sepsis (SIRS≥2, SOFA ≥ 3, procalcitonin >1,3 ng/ml). The level of hyperbilirubinemia varied from 24 to 340 mcmole/l. Violation of lipid metabolism was characterized by the increase of blood cholesterol and triglicerids level in patients of all subgroups under study. In subgroups with mechanical jaundice and acute cholangitis decrease of these indices was observed to the 7th day of the study, in the subgroup with biliary sepsis a sufficient increase was observed in all terms of the study. Low level of high density lipoproteins in patients of the three subgroups indicates the decrease of lipid forming and secretory hepatic function. As well as increase of lipoproteins of very low density and low density lipoproteins synthesized from them in patients of all three subgroups indicates violations of their transport function in cholesterin delivery into injured liver. The highest meanings of atherogenicity coefficient were stated in patients of biliary sepsis subgroup which was intense in patients of all subgroups. Conclusions. The results of lipid metabolism indices study in patients with uncomplicated mechanical jaundice and acute cholangitis indicate reversibility of hepatic dysfunction development in these patients as a result of carried out complex treatment. Lipid metabolism changes in patients with biliary sepsis indicate severe and progressing course of hepatic dysfunction accompanied by the decrease of lipid-forming and secretory hepatic function as a result of hepatocites membranes lipoprotein complex destruction which takes place under the effect of system inflammatory reply syndrome factors.
Keywords: mechanical jaundice; hepatic dysfunction; lipid metabolism